Gloria Jean's coffee in Malaysia - Abdul-Talib, Asmat-Nizam; Abdul Latif, Samshul Amry; Zakaria, Norhayati (Emerald Publishing Limited, 2011)
This case study explores the strategies employed by franchisor Gloria Jean's Coffees (GJC) in reestablishing its market presence in the Malaysian coffee market. GJC recently underwent an exchange of ownership. Under the new leadership, the company decided to appoint a new strategic master franchisee in Malaysia.